The Toyah Phase of Central Texas : Late Prehistoric Economic and Social Processes - Kenmotsu, Nancy Adele; Boyd, Douglas K. (Douglas Kevin) (Book collections on Project MUSE., 2012)
In the fourteenth century, a culture arose in and around the Edwards Plateau of Central Texas that represents the last prehistoric peoples before the cultural upheaval introduced by European explorers. This culture has been labeled the Toyah phase, characterized by a distinctive tool kit and a bone-tempered pottery tradition. Spanish documents, some translated decades ago, offer glimpses of these mobile people. Archaeological excavations, some quite recent, offer other views of this culture, whose homeland covered much of Central and South Texas. For the first time in a single vo.